Analysis of propellers for micro hydro power for domestic and comercial loads - Abid Abbas, Mohamed Arifin (2013)
The reaction turbine technology for low head application in the micro hydro power range has been vastly neglected despite niche available in scattered region of valley flows as well as in waste water canals and other energy recovery schemes, where the available head does not exceed two meters. The main objective for this study is to develop the design of propeller turbine by using Computational Fluid Dynamic (CFD) for the micro hydro power range with a particular focus on ease of manufacture. Computational Fluid Dynamic (CFD) has become the most effective tool for predicting detailed information relating the flow in turbine space to enable the selection of the best design. In present work, three dimensional turbulent real flow analysis in propeller have been carried out with variety of geometrical optimization on a propeller runner, whose blades have been designed using the free vortex theory. All the designs have been analyzes with same initial and boundary condition by using Ansys CFX computational fluid dynamic (CFD) software. This paper also presents the methodology to analyze the effect of each optimization stages. This method shows the relative changes to shaft power and water flow at constant boundary condition. The average values of flow parameters like velocities and flow angles at the inlet and outlet of runner, guide vane of turbine are computed to derive flow characteristics. It was found that the performance of the runner were got effected in the changes of geometries of the propeller. The results show the modification has increase the efficiency of propeller to catches the energy from the water from 27.2% to 55.4%.